Kanuri DP Hypothesis: A Minimalist Approach - Baba Kura Alkali Gazali (JURNAL ARBITRER, 2020)
This paper examines the structure of Kanuri DP (structure) Hypothesis within the framework of Abney (1987) and Chomsky (1995) Minimalist Programme (MP). In conducting the research, the researcher uses his native speaker intuition and other three competent native speakers of Kanuri to validate the data of this study. The study identifies Kanuri determiners as post head modifier language. The study identifies also two types of demonstrative modifiers –near and far demonstratives. The near demonstratives agree with their head nouns while the far demonstratives take both singular and plural head nouns. The far demonstratives do not show any form of agreement morphology between the nouns and their demonstrative modifiers. The analysis of DP Hypothesis shows the NP complement moves to the specifier position in the surface syntax which give rise to complement-head (C-H) order. The study further analyzes possessives, demonstratives and quantifiers under the DP hypothesis. The outcome of the study reveals that possessive determiner ‘nde’ (our) is base generated at the possessive position, moves and fills the D position under the DP in Kanuri while the far demonstrative ‘tudu’ (that) is also base generated at the Dem. Position of the determiner phrase (DP) -hence the D position is strong head position moves and fills the D position and the noun ‘fato’ (house) moves to the specifier position of the determiner phrase (DP) in order to check agreement feature in Kanuri.